Ground motion amplification pattern with TBM tunnels crossing soil-rock interface: Shaking table test - Siming Li; Roberto Cudmani; Mingqing Xiao; Zhiming Guo; Yong Yuan (Underground Space, 2023)
The current aseismic design has seldom considered the effect caused by underlain tunnels. Previous studies focused on the scenarios of tunnels embedded in homogeneous soil under transverse seismic excitation. This paper aims to investigate the tunnel effect on the surface acceleration response in soil-rock strata by shaking table tests. Three sets of excitations are employed and input along the shaking table in both transverse and longitudinal directions. The soil-rock site is classified as four micro-zones with varying conditions, to mount observation stations of acceleration sensors. Dynamic characteristics of the four zones are identified by the transfer function (TF) method, and the tunnel effect on the ground acceleration response is obtained by comparing the spectral acceleration results between the free-field and ground-tunnel models. The test results indicate that the tunnel effect varies with the site conditions. Distinctively, a significant amplification effect is observed at the A4 zone, located on the soil deposit near the soil-rock interface. Then, it is proved that the scattering waves generated at the interface and the standing waves trapped between the tunnel and upper ground surface account for the amplification, revealed by the discrepancies of the TF results and acceleration details between the free-field and ground-tunnel models.